Parental Intervention in the Marital Lives: A Case Study of STDI Imam Syafi’i Jember Students: Intervensi Orang Tua dalam Rumah Tangga: Studi Kasus Mahasiswa STDI Imam Syafi’i Jember - Muhammad Naufal Rizqi; Anjas Saputra; Muhammad Zakih; Muhammad Teguh Junaidi; Adi Akid Daulima (Al-Zaujiyyah: Jurnal Hukum Keluarga Islam, 2024)
Marriage is a very important thing in human life. Nikah in language means to combine. In the Compilation of Islamic Law, it is stated that marriage is a very strong contract or mitssaqan ghalidzan to obey the commands of Allah Subhanahu Wata'ala and carrying it out is an act of worship. One of the things that happens a lot in marriage is parental intervention in children's households. Intervention can be defined as the act of implementing a parenting plan by caring for the child in the family or in a child social welfare institution. Sekolah Tinggi Dirasat Islamiyah (STDI) Imam Syafi'i Jember is one of the universities located in Sumbersari sub-district, Jember district, province. East Java Province. The purpose of this study is to determine the phenomenon of Parental Intervention in the Household of Students of STDI Imam Syafi'i Jember, the impact of intervention, as well as the opinion of classical and contemporary scholars about parental intervention in the household of children. This research uses a qualitative approach with the type of case study research. The results of this study indicate that: (1) The phenomenon of parental intervention is divided into 2 parts; the form of intervention and the reasons why parents intervene. (2) Parental intervention has positive and negative impacts in children's households. (3) The opinions of classical and contemporary scholars are divided into 2 parts; allowed and not allowed if it leads to something bad.